Creating Numeracy Questions in Madurese Traditional Games Context: A Primary School Teachers Perspective - Sitti Karimah Sulfiah; Nur Hasanah; Layli Nur Qudrati; Jauharotul Wadiah (Didaktik Matematika, 2025)
This study used qualitative research and descriptive approach in accordance with the research objectives, namely describing the perceptions of elementary school teachers towards numeracy literacy in the context of traditional Madurese games. The instruments used were questionnaire of teachers' initial understanding, problem posing test and interview guideline. The questionnaire is used to find out the teacher's initial understanding of numeracy literacy and ethnomathematics and its implementation in learning, the problem possing test is used to see the teacher's ability to design numeracy literacy questions in the context of traditional Madurese games, and interviews are used to strengthen the data from filling out questionnaires and problem possing tests. The subjects in this study were grade 4, 5 and 6 teachers in elementary schools located in rural and urban areas. The results showed that there is no difference in understanding between rural and urban teachers regarding numeracy literacy, they can understand numeracy literacy and usually implement it in learning. However, for ethnomathematics, rural teachers cannot understand, both rural and urban teachers have never implemented ethnomathematics in learning. Finally, neither rural nor urban teachers can design numeracy literacy questions in the context of traditional Madurese games